Tanggapan Pemilih Pemula terhadap Pesan Pendidikan Politik pada Film “Kejarlah Janji” Jelang Pemungutan Suara Pemilu 2024 Studi Kasus Siswa SMKN 5 & SMAN 10 Bandung - Kenmada Widjajanto; Atalia Praratya (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
One year before the 2024 General Election, the General Elections Commission (KPU) released a politically educational film entitled “Kejarlah Janji” directed by the renowned filmmaker Garin Nugroho. The film is presented in a comedy-drama genre, portraying the intricacies of village head elections and conveying numerous political moral messages. Specifically, the KPU targeted the screening of “Kejarlah Janji” to first-time voters by organizing joint viewing events at various schools and universities across Indonesia. This article aims to examine the responses of first-time voters, in this case students of SMKN 5 and SMAN 10 Bandung, toward the moral messages conveyed in the film “Kejarlah Janji”, as well as to assess their knowledge regarding the 2024 General Election. To analyze this phenomenon, the author employs a descriptive qualitative approach based on the Social Judgment Theory, which assumes that individuals categorize messages they receive into three possible attitudes: acceptance, rejection, or non-commitment. The results of the qualitative data analysis indicate that first-time voters, specifically students of SMKN 5 Bandung, perceive both positive and negative moral messages from the film and tend to accept these moral messages. However, the film’s moral messages do not appear to correlate with first-time voters’ knowledge or awareness of the voting procedures. Some participants admitted that they lacked understanding regarding the voting process in the 2024 General Election. These findings suggest that the moral messages of “Kejarlah Janji” can be effectively received by first-time voters, yet they do not necessarily enhance their procedural knowledge of the election.